Acute Toxicity and Sublethal Effects of Lemongrass Essential Oil and Their Components against the Granary Weevil,Sitophilus granarius - Plata-Rueda, Angelica; Rolim, Gabriela Da Silva; Wilcken, Carlos Frederico [UNESP]; Zanuncio, Jose Cola; Serrao, Jose Eduardo; Martinez, Luis Carlos (Mdpi, 2020)
In the present work, we evaluate the toxic and repellent properties of lemongrass (Cymbopogon citratus(DC. ex Nees) Stapf.) essential oil and its components againstSitophilus granariusLinnaeus as an alternative to insecticide use. The lethal dose (LD(50)and LD90), survivorship, respiration rate, and repellency on adults ofS. granariusexposed to different doses of lemongrass oil and some of its components were evaluated. The chemical composition of the essential oil was found to have the major components of neral (24.6%), citral (18.7%), geranyl acetate (12.4%), geranial (12.3%), and limonene (7.55%). Lemongrass essential oil (LD50= 4.03 mu g center dot insect(-1)), citral (LD50= 6.92 mu g center dot insect(-1)), and geranyl acetate (LD50= 3.93 mu g center dot insect(-1)) were toxic toS. granariusadults. Survivorship was 99.9% in insects not exposed to lemongrass essential oil, decreasing to 57.6%, 43.1%, and 25.9% in insects exposed to LD(50)of essential oil, citral, and geranyl acetate, respectively. The insects had low respiratory rates and locomotion after exposure to the essential oil, geranyl acetate, and citral. Our data show that lemongrass essential oils and their components have insecticidal and repellent activity againstS. granariusand, therefore, have the potential for application in stored grain pest management schemes.
Keywords: gas chromatography; lethal effect; natural products; repellency; respiration rate; stored product pest